Medical Ethics Implementation of Health Services in The Digital Era: A Challenge of Health Revolution - Cut Khairunnisa; Asmaul Husna, Cut; Maulana Ikhsan; Aryandi Darwis; Andi Saputra (Lembaga Pusat Studi Sosial dan Humaniora [LPS2H], 2025)
Technological advances have played an important role in the advancement of health care, resulting in changes in the methods of interaction between doctors and patients, the procedures for establishing disease diagnosis and changes in the management of medical information. The current reliance on technology raises ethical dilemmas, privacy and data protection, medical consent, social inequality, medical consultation, empathy, and sympathy. This study aims to assess various information about the ethical challenges that healthcare workers will face in the digital era. This research is a literature review using a descriptive narrative approach. Data collection was conducted by searching online and through electronic media from various sources, including theses, dissertations, scientific publications, and e-books. Ethical challenges faced by health workers start from doctor-patient communication patterns, physical examinations, supporting examinations, diagnosis and even medical information management, which have all evolved towards digitalisation. These ethical challenges include ethical aspects of interaction patterns through telemedicine, medical support examinations, the use of electronic medical records, disease management and maintaining the confidentiality of medical information that is prone to leakage.